Enhance Watershed Segmentation for Primary Medical Imaging - Mungkala, Chuanpit (Progress in Applied Science and Technology, 2023)
In this research, we consider the problem of reducing diagnostic errors in medical imaging using an improved watershed segmentation technique. The proposed method deployed in this research depends on river basin changes and it also combines the line break method, Thresholding, and active contour method. Different shapes and operators are used for the separation to avoid changes in excess divisions in the basin. Performance measurements for image processing and watershed segmentation were made. The outcomes demonstrated that the performance of the watershed segmentation was better to that of the image processing.